A Novel Technical Protocol for Improved Capture of the Genicular Nerves by Radiofrequency Ablation. Issue 11 (27th May 2019) - Conger, Aaron; Cushman, Daniel M; Walker, Kortnie; Petersen, Russell; Walega, David R; Kendall, Richard; McCormick, Zachary L
Abstract: Background: Fluoroscopically guided cooled genicular nerve radiofrequency ablation (RFA) is an increasingly performed procedure for chronic, refractory knee pain due to osteoarthritis. Traditionally, partial sensory denervation has been accomplished through ablation of the superomedial, superolateral, and inferomedial genicular nerves. However, recent cadaveric studies have demonstrated additional sensory nerves and significant anatomic variation that impact current protocols. Objective: We describe an updated cooled genicular nerve radiofrequency ablation protocol that accounts for varied nerve location of the superomedial, superolateral, and inferomedial genicular nerves, as well as capture of the terminal articular branches of the nerves to the vastus intermedius, vastus lateralis, and vastus medialis. Furthermore, we describe an adjusted technique for inferomedial genicular nerve capture that mitigates the risk of pes anserine tendon injury. Design: Technical report and brief literature review. Methods: Cadaveric studies relating to the sensory innervation of the anterior knee joint were reviewed, and a more accurate and comprehensive cooled genicular nerve radiofrequency ablation (CRFA) protocol is proposed. Conclusions: Based on recent, rigorous anatomic dissections of the knee, the proposed genicular nerve CRFA protocol will provide more complete sensory denervation and potentially improve clinical outcomes. Prospective studies will be needed to confirm the hypothesis that this protocol will result in improved effectiveness and safety of genicular nerve RFA.